Pregnancy with chronic myeloid leukemia: case report and literature review - Chowdhury, Tanzeem Sabina; Jerin, Israt; Chowdhury, T. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Chronic myeloid leukemia (CML) is a rare condition during reproductive age. Still, women may present with pre-existing or newly diagnosed CML during pregnancy. The management of chronic myeloid leukemia during pregnancy requires balancing the well-being of the mother with that of fetus. Tyrosine Kinase inhibitors are considered the most effective drug against CML but they are still not considered safe during pregnancy and breast feeding. So, there is a need for management of CML with alternate drugs during pregnancy. Here we report a case of a 26-year-old lady who was diagnosed with chronic myelogenous leukemia (CML) at 20 weeks of gestation and had an atypical chromosome translocation t (9:22). She was managed jointly by obstetrician and haemato-oncologist for the remainder of her pregnancy and eventually she delivered a healthy baby at term.